Fundamentalisme dan Gerakan Radikal Islam Kontemporer: Kasus Jama’ah Islamiyah di Indonesia - Huda, Miftahul (UIN Maulana Malik Ibrahim Malang, 2007)
The phenomenon of fundamentalism and radicalism at least can be seen in the case of Jemaah Islamiyah in Indonesia. Whether or not Jemaah Islamiyah has a link with Al-Qaeda headed by Osama Bin Laden, obviously its movement has affiliations not only in Indonesia, but also in Malaysia, Singapore, and South Philippine, and even in Thailand, Burma, and Brunei. Jemaah Islamiyah is believed to be established by Abdullah Sungkar in Malaysia in 1994/1995 aiming for establishing an Islamic State. Jemaah Islamiyah is the realization of Hybrid ideology inspired by some other movements, such as Egypt Radical Moslem, Darul Islam Movement, Dewan Dakwah Islamiyah Indonesia (DDII). This movements view the effort of Christian missionary as a threat to Islam. Fenomena fundamentalisme dan radikalisme setidaknya bisa dilihat dalam kasus Jemaah Islamiyah di Indonesia. Benar atau tidaknya Jemaah Islamiyah berkaitan dengan Al Qaeda yang diketuai oleh Osama bin Laden, pergerakannya jelas-jelas tak hanya di Indonesia, tetapi juga di Malaysia, Singapura, dan Filipina Selatan, bahkan di Thailand, Burma, dan Brunei. Jemaah Islamiyah didirikan oleh Abdullah Sungkar di Malaysia pada tahun 1994/1995 dengan tujuan mendirikan negara Islam. Jemaah Islamiyah adalah realisasi dari ideologi hibrid yang terinspirasi oleh beberapa gerakan lainnya, seperti Muslim Radikal Mesir, Pergerakan Darul Islam, Dewan Dakwah Islamiyah Indonesia (DDII). Pergerakan ini beranggapan bahwa usaha misionaris Kristen sebagai ancaman bagi Islam.